Application of Local Potential in the Design of Selondang Kelapa Floating Market Area as an Icon of Tembilahan City - Annisa Hidayatul Islami; Dwi Lindarto Hadinugroho (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Selondang Kelapa Market is the main market in Tembilahan City, the fire incident in 2019 caused this market lose its vital function. The of the Selondang Kelapa Market aims to re-optimize the function of the market as before and develop it into a market with modern buildings and as regional tourism destination. The application of Tembilahan’s local potential and the Neo-Vernacular Architecture theme to buildings is expected to make the Selondang Kelapa Floating Market a city icon and landmark in Tembilahan City.